Geological characteristics of coal mines in the Zagros Basin of Iran: Unveiling rock mechanical properties and time-dependent behavior - Alireza Khoshmagham; Navid Hosseini Alaee; Reza Shirinabadi; Amir Hossein Bangian Tabrizi; Mehran Gholinejad; Pooria Kianoush (Energy Geoscience)
The Zagros Basin in southwestern Iran is a significant source of coal, with numerous coal mines operating in the region. Ensuring the stability of coal mines is crucial for safe and efficient mining operations. This study investigates the time-varying response of rocks and roof resistance in coal mines in the Zagros Mountains using a novel approach that combines numerical simulation, relaxation testing, and rock displacement studies. The results show that rocks exhibit significant time-dependent behavior, with changes in rock mechanical properties over time. A comprehensive viscoelastic-plastic model is developed to accurately describe the time-varying strain-softening response of rocks and simulate laboratory tests. The model integrates the Burgers and strain-softening models, simulating stress relaxation curves and rock displacement over time. The study reveals that the rock mass displays significant nonlinear behavior, with changes in rock mechanical properties over time. The findings of this study highlight the importance of considering the time-varying response of rocks and roof resistance in coal mine stability analysis. The results provide valuable insights into the time-dependent behavior of rock mass in coal mines in Iran, which can inform mining practices and mitigate potential hazards. Results in this study can contribute to developing strategies for improving roof stability and reducing the likelihood of roof collapses.